The factors influencing the demand of Family Takaful product in Rawang, Selangor / Syafiqah Nordin - Nordin, Syafiqah (2015)
This research is about the factors that influence the demand of Family Takaful product in Rawang. The objective of these research are to identify the level of the demand of Family Takaful product amongst people in Rawang, to identify the factors that influence the demand of the Family Takaful product amongst people in Rawang, and to determine the most significant factors that influence the demand of the Family Takaful product amongst people in Rawang. The independent variable for these research such as the level of the income, the knowledge and the marketing and advertising. It is will be identify in order to make an investigated whether the independent variables have significant and influenced to the public employees amongst governance and private sector in Rawang. This study was conducted in resident area which in located in Rawang. The questionnaire will be distributed randomly to 70 respondent. To obtain the data, the researcher was used two methods that are primary and secondary data. Data will be analyzed by using the reliability test, Pearson correlation analysis and Multiple Regression Analysis.